2016
DOI: 10.1177/0146167216649606
|View full text |Cite
|
Sign up to set email alerts
|

When It’s Okay That I Don’t Play

Abstract: Being excluded and ignored has been shown to threaten fundamental human needs and cause pain. Such reflexive reactions to social exclusion have been conceptualized as direct and unmoderated (temporal need threat model of ostracism). Here, we propose an extension and argue that reflexive reactions depend on how social exclusion situations are construed. If being excluded is understood as a violation of an inclusion norm, individuals will react with pain and threat. In contrast, if being excluded is consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 46 publications
4
64
0
5
Order By: Relevance
“…This result is in line with findings from prior experimental research, which show that if exclusion is consistent with social as well as one’s personal norms and attitudes, then negative affective reactions are attenuated or even dissipate altogether [8]. As a potential caveat, in should be noted that there might be variation in what participants thought about when they answered questions about “immigration attitudes,” especially whether they included themselves in that category or not.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This result is in line with findings from prior experimental research, which show that if exclusion is consistent with social as well as one’s personal norms and attitudes, then negative affective reactions are attenuated or even dissipate altogether [8]. As a potential caveat, in should be noted that there might be variation in what participants thought about when they answered questions about “immigration attitudes,” especially whether they included themselves in that category or not.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has indicated that individuals can remember as well as relive social exclusion experiences very accurately [71]. For reasons of test efficiency, Need Fulfillment and Mood were assessed with short scales [8]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations